THE IMPACT OF QUR'ANIC READING HABITS ON MAḤĀRAH QIRĀ'AH SKILLS OF MADRASAH IBTIDAIYAH STUDENTS IN MENTENG-NORTH SUMATERA - Mitra, Rohma (Universitas Islam Negeri Sumatera Utara Medan, 2024)
This study aims to examine the influence of Qur'anic reading habits on the maharah qira'ah (Arabic reading skills) of students at Madrasah Ibtidaiyyah (MI) in Menteng, Medan. The background of this research is grounded in the importance of reading proficiency in Arabic language education, along with the limited number of quantitative studies that link religious habits with students' linguistic achievement. This research employs a quantitative correlational approach. Data were collected through a questionnaire measuring Qur'anic reading habits and a qira'ah test assessed using a rubric that evaluated aspects such as articulation (makhraj), reading accuracy, fluency, and vocabulary mastery (mufradat). A purposive sample of 30 MI students was selected. The results of the validity and reliability tests confirmed that the instruments used were both valid and reliable. The Spearman correlation analysis revealed a coefficient of rs = 0.8055 with a p-value < 0.01, indicating a very strong and statistically significant relationship between Qur'anic reading habits and maharah qira'ah. These findings suggest that regular engagement with Qur'anic reading contributes not only to students' spiritual growth but also positively influences their Arabic reading proficiency. This study offers meaningful insights for the development of Arabic language teaching strategies that are integrated with religious practices.